Induction of apoptosis in melanoma A375 cells by a chloroform fraction of Centratherum anthelminticum (L.) seeds involves NF-kappaB, p53 and Bcl-2-controlled mitochondrial signaling pathways. - Leong, K.H. (BioMed Central, 2013)
Centratherum anthelminticum (L.) Kuntze (scientific synonyms: Vernonia anthelmintica; black cumin) is one of the ingredients of an Ayurvedic preparation, called “Kayakalp”, commonly applied to treat skin disorders in India and Southeast Asia. Despite its well known anti-inflammatory property on skin diseases, the anti-cancer effect of C. anthelminticum seeds on skin cancer is less documented. The present study aims to investigate the anti-cancer effect of Centratherum anthelminticum (L.) seeds chloroform fraction (CACF) on human melanoma cells and to elucidate the molecular mechanism involved.The MTT assay showed that CACF dose-dependently inhibited cell growth of A375, while exerted less cytotoxic effect on normal primary epithelial melanocytes. We demonstrated that CACF induced cell growth inhibition through apoptosis, as evidenced by cell shrinkage, increased annexin V staining and formation of membrane blebs. CACF treatment also resulted in higher reactive oxygen species (ROS) production and lower Bcl-2 expression, leading to decrease mitochondrial membrane potential (MMP). Disruption of the MMP facilitated the release of mitochondrial cytochrome c, which activates caspase-9 and downstream caspase-3/7, resulting in DNA fragmentation and up-regulation of p53 in melanoma cells. Moreover, CACF prevented TNF-α-induced NF-κB nuclear translocation, which further committed A375 cells toward apoptosis.